Levobupivacaine versus racemic bupivacaine: a comparative study on spinal anaesthesia in lower limb surgeries - Imam, Md. Arshad; Hasnat, Sabir (International Journal of Research in Medical Sciences, 2017)
Background: This study aims to compare the anaesthetic potency of intrathecally administered levobupivacaine with racemic bupivacaine in lower limb surgeries. Methods: 60 adult cases ranging in age from 18 to 60 years with ASA Grade I and II, presenting for elective lower limb surgery were randomly allocated into two groups containing 30 cases each. Cases in Group L received 3ml of 0.5% levobupivacaine and those in Group R received 3ml of 0.5% levobupivacaine. Results: Cases in both groups showed similarity and no statistically significant differences were observed. Cardiovascular parameters were stable and similar between both groups. Conclusions: Levobupivacaine and racemic bupivacaine show equally effective potencies for spinal anaesthesia in lower limb surgeries.